Development of Flipbook-Based E-Module Integrated with External Features to Facilitate Student Self-Learning - Firdha Yusmar; Pramudya Dwi Aristya Putra; Nur Ahmad; Sri Rejeki Dwi Astuti (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2024)
This study aims to develop a flipbook-based E-Module integrated with external features to facilitate student self-learning. This research uses a Research and Development (R&D) method with an ADDIE model, which consists of five stages, i.e., analyze, design, develop, implement, and evaluate. The needs analysis of teaching material development was conducted through surveys, interviews, and observations. The validity test used a validation instrument filled out by three experts. Practicality was measured using the results of a questionnaire filled out by students as respondents. The data collected were then analyzed quantitatively. The results showed that the flipbook-based E-Module integrated with external features was categorized as very valid with a percentage of 91.09% and very practical with a score of 90.14%. Flipbook-based E-Module facilitated student self-learning in accordance with its character, namely self-instructional, self-contained, stand-alone, adaptive, and user-friendly characteristics.